Partners with benefits: when multinational corporations succeed in authoritarian courts - Chen, Frederick R. (2023)
Scholars often assume that courts in authoritarian regimes cannot credibly protect foreign investors' interests because these institutions lack judicial independence. In this article, we construct a novel data set on multinational corporations' litigation activities in Chinese courts from 2002 to 2017. This supports the first systematic case-level analysis of foreign firms' lawsuit outcomes in an authoritarian judiciary. We find that foreign companies frequently engage in litigation in authoritarian courts. Moreover, we theoretically and empirically distinguish between two types of government-business ties in terms of their effectiveness in incentivizing the host state to protect foreign investors' interests. We argue that ad hoc, personal political connections deliver only trivial lawsuit success for multinational enterprises, while formal corporate partnerships with regime insiders can lead the state to structurally internalize foreign investors' interests. In particular, we demonstrate that joint venture partnerships with state-owned enterprises help foreign firms obtain more substantial monetary compensation than other types of multinational enterprises. By contrast, the personal political connections of foreign firms' board members do not foster meaningful judicial favoritism. These findings are robust to tests of alternative implications, matching procedures, and subsample robustness checks. This article advances our understanding of multinational corporations' political risk in host countries, government-business relations, and authoritarian judicial institutions.